Nitric Oxide in Migraine - L. Neeb; U. Reuter (CNS & Neurological Disorders - Drug Targets, 2007)
The potent vasodilatator and messenger molecule nitric oxide (NO) is believed to play a key role in migraine pathogenesis. NO donors such as glyceryl trinitrate (GTN) can cause headache. Infusion of GTN leads to a migraine attack in migraineurs with a latency of 4 to 6 hours. In this review we focus in the role of nitric oxide and the transcription factor nuclear factor-κB (NF-κB) in migraine pathophysiology in humans and animal models. NO is involved in pain transmission, hyperalgesia, chronic pain, inflammation and central sensitization mostly in a cyclic guanosinemonophosphate (cGMP) dependent way. We aim to illustrate how NO is implicated in the induction of a migraine attack in migraineurs and how experimental animal models may help to elucidate the mechanisms of the human GTN response. Because of the role of NO in migraine we try to assess if and how the action of preventative migraine drugs involves the NO pathways. More knowledge about the involvement of NO in the genesis of migraine headache may also provide possible future therapeutic targets for acute migraine therapy.
Keywords: migraine